2022
DOI: 10.1097/brs.0000000000004339
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Telemedicine Utilization in Spine Surgery

Abstract: An expert panel of spine surgeons had consensus that video-based telemedicine could be utilized regardless of patient location, is sufficient for evaluation and indication of surgery for multiple common spine pathologies, such as lumbar stenosis, lumbar radiculopathy, as well as cervical radiculopathy, and could be appropriate for various visit types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This finding highlights the fact that telemedicine only preoperative assessment may not be appropriate for all types of diagnoses, especially ones that are highly dependent on the physical examination, such as cervical myelopathy. Indeed, a recent consensus study has shown that spine surgeons had consensus that an in-person visit before surgery is necessary after initial video telemedicine evaluation for cervical myelopathy 18. In addition, the surgeons had consensus that special tests for myelopathy were not possible to perform over a video-based visit 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding highlights the fact that telemedicine only preoperative assessment may not be appropriate for all types of diagnoses, especially ones that are highly dependent on the physical examination, such as cervical myelopathy. Indeed, a recent consensus study has shown that spine surgeons had consensus that an in-person visit before surgery is necessary after initial video telemedicine evaluation for cervical myelopathy 18. In addition, the surgeons had consensus that special tests for myelopathy were not possible to perform over a video-based visit 18.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, the surgeons had consensus that special tests for myelopathy were not possible to perform over a video-based visit. 18 However, no consensus was reached on whether or not an in-person evaluation before surgery was necessary for lumbar stenosis and lumbar radiculopathy. 18 All together, these findings suggest that patients with lumbar stenosis or radiculopathy may be appropriately indicated for surgery through telemedicine alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published consensus document, we surveyed an international panel of spine surgeons using Delphi methodology to determine the visit types and diagnoses that could be evaluated using telemedicine. 6 The results demonstrated that patients with lumbar stenosis and lumbar radiculopathy could be indicated for surgery following a telemedicine evaluation. These findings are in keeping with data showing that surgical plans generally do not change for spine patients who had a virtual encounter prior to in-person pre-surgery evaluation.…”
mentioning
confidence: 93%
“…The same study suggested that for cervical myelopathy (where reflex and special testing is relatively more important) and adult deformity, an in-person evaluation is necessary prior to recommending surgery. 6 …”
mentioning
confidence: 99%